MEDAN MAKNA VERBA MELIHAT DALAM BAHASA MELAYU SANGGAU - Evi Novianti (Balai Bahasa Kalimantan Barat, 2018)
This study aims to describe the lexeme verb ‘see’ in Sanggau Malay language. The method applied is descriptive in the form of qualitative research. The data in this study are words containing verb meanings ‘see’ in Sanggau Malay language. The source of the data in this study is the Sanggau Malay language spoken by Sanggau Malay speakers. The data collected used images and questionnaires and see proficient involvement. Data collection tools in the form of vocabulary lists, images, note cards, questionnaires, and recording devices. The field of verb meanings in Sanggau Malay consists of 17 lexemes. Of the 17 lexemes, 12 verb lexemes ‘see’ without using tools and 5 verb lexemes ‘see’ using a tool.